Practice guideline update summary: Acute treatment of migraine in children and adolescents: Report of the Guideline Development, Dissemination, and Implementation Subcommittee of the American Academy of Neurology and the American Headache Society. Issue 8 (17th September 2019) - Oskoui, Maryam; Pringsheim, Tamara; Holler‐Managan, Yolanda; Potrebic, Sonja; Billinghurst, Lori; Gloss, David; Hershey, Andrew D.; Licking, Nicole; Sowell, Michael; Victorio, M. Cristina; Gersz, Elaine M.; Leininger, Emily; et al.
Abstract : Objective: To provide evidence‐based recommendations for the acute symptomatic treatment of children and adolescents with migraine. Methods: We performed a systematic review of the literature and rated risk of bias of included studies according to the American Academy of Neurology classification of evidence criteria. A multidisciplinary panel developed practice recommendations, integrating findings from the systematic review and following an Institute of Medicine‐compliant process to ensure transparency and patient engagement. Recommendations were supported by structured rationales, integrating evidence from the systematic review, related evidence, principles of care, and inferences from evidence. Results: There is evidence to support the efficacy of the use of ibuprofen, acetaminophen (in children and adolescents), and triptans (mainly in adolescents) for the relief of migraine pain, although confidence in the evidence varies between agents. There is high confidence that adolescents receiving oral sumatriptan/naproxen and zolmitriptan nasal spray are more likely to be headache free at 2 hours than those receiving placebo. No acute treatments were effective for migraine‐related nausea or vomiting; some triptans were effective for migraine‐related phonophobia and photophobia. Recommendations: Recommendations for the treatment of acute migraine in children and adolescents focus on the importance of early treatment, choosing the route of administration best suited to the characteristics of the individual migraine attack, and providing counselling on lifestyle factors that can exacerbate migraine, including trigger avoidance and medication overuse.